The Relationship between Stroke Metrics, Work Rate and Performance in Slalom Kayakers - Macdermid PW; Olazabal T (MDPI (Basel, Switzerland), 2022)
The purpose of this study was to assess the relationship between work rate, stroke metrics, and performance in whitewater slalom. Twelve Spanish, nationally competitive whitewater slalom kayakers took part in a simulated competition while using an instrumented kayak paddle to record stroke metrics over a simulated race, total duration and sectional splits. Performance time was highly correlated to overall power output (r2 = 0.511, p < 0.001), where kayakers demonstrated a positive pacing strategy with power output significantly decreasing over successive sectional splits (158 ± 40, 112 ± 32 and 65 ± 33 W, p < 0.001). This resulted in an increased stroke duration (p < 0.001), time to peak force (p < 0.001), a decrease in stroke peak force (p < 0.001), and rate of peak force development (p < 0.001) over elapsed time. As such, work rate is deemed an objective metric to monitor performance, prescribe training, and ascertain optimal pacing strategies in canoe slalom.
Keywords: canoeing; power meter; whitewater slalom